How Reliable Are Social Safety Nets? Value and Accessibility in Situations of Acute Economic Need - Herwig Immervoll; Raphaela Hyee; Rodrigo Fernandez; Jongmi Lee (Institute of Labor Economics (IZA), 2022)
Social protection systems use a range of entitlement criteria. First-tier support typically requires contributions or past employment in many countries, while safety net benefits are granted on the basis of need. In a context of volatile and uncertain labour markets, careful and continuous monitoring of the effectiveness of income support is a key input into an evidence-based policy process. This paper proposes a novel empirical method for monitoring the accessibility and levels of safety net benefits. It focusses on minimum-income benefits (MIB) and other non-contributory transfers and relies on data on the amounts of cash support that individuals in need receive in practice. Results show that accessibility and benefit levels differ enormously across countries – for instance, more than four out of five low-income workless one-person households received MIB in Australia, France and the United Kingdom, compared to only one in five in Greece and Italy, two countries that have since sought to strengthen aspects of safety-net provisions.
Keywords: H53; H31; D31; I38; C31; C53; 330; minimum-income benefits; accessibility; coverage; non-take-up; adequacy; poverty